The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1093/embo-reports/kvd109
|View full text |Cite
|
Sign up to set email alerts
|

The β clamp targets DNA polymerase IV to DNA and strongly increases its processivity

Abstract: The recent discovery of a new family of ubiquitous DNA polymerases involved in translesion synthesis has shed new light onto the biochemical basis of mutagenesis. Among these polymerases, the dinB gene product (Pol IV) is involved in mutagenesis in Escherichia coli. We show here that the activity of native Pol IV is drastically modified upon interaction with the β subunit, the processivity factor of DNA Pol III. In the absence of the β subunit Pol IV is strictly distributive and no stable complex between Pol I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
153
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(165 citation statements)
references
References 14 publications
8
153
0
Order By: Relevance
“…1 C and D) and rate ( Fig. 2A) of each synthesis step were generated from a large number of events; the data were in agreement with previous single-molecule experiments for Pol III (22) and bulk data for Pol IV (23). Pauses between synthesis steps were exponentially distributed, consistent with a single rate-limiting step, and we observed that increasing the concentration of Pol III from 5 to 30 nM reduced the pause length ( Fig.…”
Section: Resultssupporting
confidence: 89%
“…1 C and D) and rate ( Fig. 2A) of each synthesis step were generated from a large number of events; the data were in agreement with previous single-molecule experiments for Pol III (22) and bulk data for Pol IV (23). Pauses between synthesis steps were exponentially distributed, consistent with a single rate-limiting step, and we observed that increasing the concentration of Pol III from 5 to 30 nM reduced the pause length ( Fig.…”
Section: Resultssupporting
confidence: 89%
“…E. coli contains two Y-family polymerases, PolIV and PolV; both are DNA damage inducible and belong to the SOS regulon. PolIV has an extremely low affinity for the naked primer-template substrate and heavily relies on the β clamp (a bacterial functional homolog of PCNA) to load onto DNA [87,88]. In vitro studies indicate that PolIV and its archeal homolog Dpo4 are relatively faithful polymerases at the incorporation step and the low fidelity primarily results from poor discrimination between correct and incorrect incoming nucleotides at the binding stage and the capacity to elongate mismatched primer template, which results in -1 frameshift mutations [89,90].…”
Section: Ddt In Saccharomyces Cerevisiaementioning
confidence: 99%
“…All five E. coli DNA polymerases appear to interact with the replication processivity factor, the b-clamp (Hughes et al, 1991;Kim and McHenry, 1996;Lopez de Saro and O'Donnell, 2001;Tang et al, 2000;Wagner et al, 2000). The three SOS-inducible DNA polymerases (II, IV and V) contain a short peptide (consensus motif: QLxLF) that was identified in a yeast two-hybrid screen to mediate their interaction with the b-clamp (Dalrymple et al, 2001).…”
Section: The Emerging Complexity Of Tls Pathways In Vivomentioning
confidence: 99%